The –ed allomorphs of Malay speakers of English and linguistic knowledge types - Mohammad Lotfie, Maskanah Mohammad; Abdul Kadir, Maimunah; Pilus, Zahariah (International Center for Research and Development, 2016)
Malay is a language from the Austronesian family and unlike the Indo-European-originated English; it generally does not have inflections as temporal markers. Problems are observed in the production of –ed allomorphs – [d], [t], [ɪd] or [ed] – they are pronounced differently from the Standard English variety or dropped altogether. This paper presents a study on Malay speakers’ use of –ed allomorphs in English and the relationship between the use and two types of linguistic knowledge. Data were collated from 50 respondents who were social science undergraduates. Four instruments were used to gauge the respondents’ verbal use of –ed allomorphs as well as their implicit and explicit knowledge of the said allomorphs. Results indicate that respondents’ had some knowledge of both implicit and explicit knowledge of the allomorphs. Students’ verbal usage of the English language indicates lack of approximation of the allomorphs to Standard English pronunciation. Results also suggest moderate relationship between implicit and explicit knowledge of the allomorphs and their verbal production by Malay speakers of English. The finding illuminates acquisitional problem of English language speakers whose mother tongue does not share inflectional features. The findings also provide insights to possible pedagogical solutions in helping learners of the English language to approximate Standard English and in the long run, enhance employability and effective communication.